Utilization of a Pseudo-Stochastic Model of Terrain in Simulation of Vibrations and Snubbing in Road Means of Transport - Harman, Blahoslav; Ferencey, Viktor (Communications - Scientific letters of the University of Zilina, 2003)
Physical and geometrical properties of environment lead to mathematical models of terrain- vehicle interaction. The basic idea of the presented approach is to construct a two – dimensional function whose three-dimensional graph has properties similar to the terrain to be modeled. The idea of the paper is expected to be used in simulation of phenomena connected with impacts of vibrations and snubbing to humans as well as on technological factors.